ANALISIS DIMENSI KUALITAS PELAYANAN RUMAH SAKIT UMUM DAERAH KABUPATEN BATANG - Giovani Anggasta; Herbasuki Nurcahyanto; Susi Sulandari (Journal of Public Policy and Management Review, 2014)
Community demands for public services in the health sector is still considered low into the background of this research Batang Regency’s Public Hospital. Result of observations and interviews with several informants indicate that this hospital still has a low service quality and customer satisfaction have not been optimally viewed from the dimensions of service quality. Quality improvement and quality of these services should be started from a strong commitment and high professionalism that existing systems can run optimally so as to achieve customer satisfaction.